Upaya Mengatasi Masalah Perilaku Mahasiswa Merokok Menurut Teori Psikoanalisis - Apri Yanti Kasilda Siburian; Yeni Marito; Theresia Elizasabaet Sianturi; Shyndy Monika Sianturi; Natalia Br Ginting; Ingrid Duma Sidabalok (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to determine what triggers smoking behavior among students of the Faculty of Engineering, State University of Medan. The design of this study is qualitative with a descriptive phenomenological approach. Data collection techniques are based on interviews, observations, documentation, and literature studies as research support. The source of research data is 4 active FT students, who have a smoking habit, and are willing to be informants for this study. This study refers to the Psychoanalytic Theory which consists of 3 structures: Id, Ego, and Superego. Psychoanalytic theory is used by researchers in analyzing cases of factors that trigger students to smoke, as well as analyzing research discussions. The results of the study showed that the factors behind students smoking were environmental influences, peers, and psychological satisfaction.